The Use of ARIAS Teaching Model to Improve the Reading Comprehension of First Grade Students of SMAN I Poli Polia in 2015/ 2016 Academic Years - Nur Indah, Wa Ode Siti; Sidu Marafat, La Ode; Tambunan, Tambunan (Halu Oleo University, 2016)
This study aims to improve the students reading comprehension, the students activity, and made students have a positive perception about English learning process through ARIAS teaching model to the first grade students of SMAN Poli-Polia I East Kolaka in the academic year of 2015/2016. The design of this study is Classroom Action Research. The steps of this study are planning, conducting action, observation, and reflection. The subjects of the research were 36 students of grade X Mia 3 at SMAN Poli-Polia I East Kolaka. The instruments of this study are the observation sheet, interviews, field notes, reading test and questionnaire. In reference to the actions conducted in two cycles, it is evident that ARIAS teaching model could improve students’ reading comprehension as justified in the following results. First, there is an improvement on students’ activity. Most of students are active in teaching and learning process (70% students actively participate in reading comprehension activities). Second, most students of grade X Mia 3 have positive perception in English learning process Third, there is an improvement on students’ reading comprehension as it is displayed in the increase of the mean score (the result of the cycle II was 75.49 compared to the result of the cycle I was 64.71). In conclusion, ARIAS teaching model could improve the students’ reading comprehension.